Analysis of Teacher Difficulties in Real Action Performance On the Merdeka Teaching Platform (PMM) at SDN 187/I Teratai Muara Bulian - Anesya Marito; Destrinelli; Hendra Budiono (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2025)
This study aims to analyze the difficulties faced by teachers in implementing real action performance on the Merdeka Mengajar Platform (PMM) at SDN 187/I Teratai Muara Bulian. The research employs a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving teachers and the school principal as research subjects. The results indicate that the implementation of real action still faces several obstacles, including teachers' low understanding of technology, time constraints due to administrative workloads, and a lack of motivation and appreciation for their work. Additionally, some teachers struggle to adapt to the use of PMM, particularly in structuring real actions that meet established standards. To address these challenges, schools need to enhance training, provide mentorship, and offer incentives to boost teacher motivation. These measures are expected to optimize the use of PMM, thereby improving the quality of primary education.